Investigation into the Gelation of Polyacrylonitrile Solution Induced by Dry-jet in Spinning Process and Its Effects on Diffusional Process in Coagulation and Structural Properties of Carbon Fibers - Shin, Keon-Ah; Park, Sejoon; Huong Thi Bich Nguyen; Lee, Joong Hee; Lee, Sungho; Joh, Han-Ik; Jo, Seong Mu (한국고분자학회, 2018)
The jet effect in dry-jet wet spinning of a polyacrylonitrile (PAN) solution was investigated. The two parameters, jet-stretch ratio and air gap length, of the jet were controlled to elucidate each effect on PAN precursors and resulting carbon fibers. Excessively high jet-stretch ratio (> 4) or air-gap (> 1 cm) resulted in the development of the internal pore structure in PAN precursors. The pores remained even after the densification by thermal treatment acting as defects for poor tensile properties of carbon fibers (CFs). It was revealed that two parameters critically controlled the bidirectional diffusion of both solvent and non-solvent by determining the degree of the surface gelation at the jet. Excessively high jet-stretch ratio or high air-gap length created a thick solid skin on extruded dope limiting solvent/non-solvent diffusion. As a method to limit the development of the pores under the condition of high jet stretch ratio (> 4), raising the dope temperature for limiting the degree of gelation at the jet was attempted and successfully manufactured mechanically improved fiber with a dense structure without pores under high jet-stretch condition. The study suggests that the high quality PAN precursors for high performance CFs can be manufactured under high jet-stretch ratio condition with proper management on gelation at the jet.